2012
DOI: 10.1186/1471-2164-13-252
|View full text |Cite
|
Sign up to set email alerts
|

A hemocyte gene expression signature correlated with predictive capacity of oysters to survive Vibrio infections

Abstract: BackgroundThe complex balance between environmental and host factors is an important determinant of susceptibility to infection. Disturbances of this equilibrium may result in multifactorial diseases as illustrated by the summer mortality syndrome, a worldwide and complex phenomenon that affects the oysters, Crassostrea gigas. The summer mortality syndrome reveals a physiological intolerance making this oyster species susceptible to diseases. Exploration of genetic basis governing the oyster resistance or susc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 48 publications
3
25
0
1
Order By: Relevance
“…This is consistent with previous studies. Also, in previous studies, the haemocyte gene expression was able to predict the capacity of oysters to survive infections by the pathogenic Vibrio strains (Rosa et al 2012). From our results, we can put forward a hypothesis that the oyster antioxidant enzyme gene expressions may be used to evaluate long-term mortalities.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…This is consistent with previous studies. Also, in previous studies, the haemocyte gene expression was able to predict the capacity of oysters to survive infections by the pathogenic Vibrio strains (Rosa et al 2012). From our results, we can put forward a hypothesis that the oyster antioxidant enzyme gene expressions may be used to evaluate long-term mortalities.…”
Section: Discussionsupporting
confidence: 51%
“…Emails: lili@qdio.ac.cn; gfzhang@qdio.ac.cn to be associated with large-scale summer mortalities in oysters (Garnier et al 2007) and are widely used for experimental oyster infection (Gay et al 2004b;Garnier et al 2008). Transcriptomic and genomic approaches have also been used for the characterization of the oyster defence mechanisms in response to infection by these two strains (de Lorgeril et al 2011;Rosa et al 2012). Vibrio tubiashii (Hada et al 1984) has been found to be responsible for serious disease in North American hatchery-reared C. gigas (Estes et al 2004;Elston et al 2008).…”
Section: Comparative Analysis Of Oyster (Crassostrea Gigas) Immune Rementioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, the first sequencing of C. gigas genome [78] and various transcriptomic studies allowed to identify a vast range of potential effectors and key actors of oyster immunity [62,94,125e127]. On the other hand, the development of genomic technologies such as high throughput RT-qPCR analyses allowed to explore the expression of numerous immune-related genes at the individual levels revealing an extraordinary polymorphism in basal expression of some of them in this species [128]. Indubitably, analyses performed at individual level may give new light on the genetic bases of oyster immune response and reveal its diversity and complexity.…”
Section: Individual Polymorphism Of Gene Expression and Genetic Strucmentioning
confidence: 99%
“…Another disease of adult bivalves associated with exposure 640 to pathogens (including vibrios) combined with environmental 641 stress is summer mortality (Barbosa et al, this issue). A few tran-642 scriptomic studies have looked at the responses of Pacific oysters 643 to challenge with vibrio species associated with summer mortality, 644with the goal of determining potential mechanisms of resistance to 645 summer mortality(de Lorgeril et al, 2011;Rosa et al, 2012). All 646 these transcriptomic studies have led to the identification of genes 647 and molecular processes potentially involved in resistance to bac-648 terial diseases in bivalves.…”
mentioning
confidence: 99%